CDK digital marketing : addressing channel conflict with data analytics - Zettelmeyer, Florian; Merkley, Greg ([London] : SAGE, 2016)
Four years into a five-year contract with General Motors to be the exclusive website vendor to its U.S. network of more than 4,000 dealers, CDK Digital faced a crucial contract renewal at the end of 2012. The case follows Melissa McCann, director of strategic marketing, and Chris Reed, CMO, as they prepared for a critical meeting in July 2011: a presentation to the customer relationship management (CRM) subcommittee of the Chevrolet dealer council.
Originally Published in: Zettelmeyer, F., & Merkley, C. (2014). CDK Digital Marketing: Addressing Channel Conflict with Data Analytics. 5-314-504. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; CDK Digital (Firm); Technological innovations -- Case studies; Industrial marketing -- Case studies; Marketing channels -- Case studies